Structure–function relationship of dynorphin B variants using naturally occurring amino acid substitutions - Zangrandi, Luca; Fogli, Barbara; Mutti, Anna; Staritzbichler, René; Most, Victoria; Hildebrand, Peter W.; Heilbronn, Regine; Schwarzer, Christoph (Frontiers in Pharmacology, 2024)
Dynorphins (Dyn) represent the subset of endogenous opioid peptides with the highest binding affinity to kappa opioid receptors (KOPr). Activation of the G-protein coupled pathway of KOPr has strong anticonvulsant effects. Dyn also bind to mu (MOPr) and delta opioid receptors (DOPr) with lower affinity and can activate the -arrestin pathway. To fully exploit the therapeutic potential of dynorphins and reduce potential unwanted effects, increased selectivity for KOPr combined with reduced activation of the mTOR complex would be favorable. Therefore, we investigated a series of dynorphin B (DynB) variants, substituted in one or two positions with naturally occurring amino acids for differential opioid receptor activation, applying competitive radio binding assays, GTPγS assays, Presto-Tango, and Western blotting on single opioid receptor-expressing cells. Seven DynB-derivatives displayed at least 10-fold increased selectivity for KOPr over either MOPr or DOPr. The highest selectivity for KOPr over MOPr was obtained with DynB_G3M/Q8H, the highest selectivity for KOPr over DOPr was obtained with DynB_L5S. Increased selectivity for KOPr over MOPr and DOPr was based on a loss of affinity or potency at MOPr and DOPr rather than higher affinity or potency at KOPr. This suggests that the investigated amino acid exchanges in position 3, 5 and 8 are of higher importance for binding and activation of MOPr or DOPr than of KOPr. In tests for signal transduction using the GTPγS assay, none of the DynB-derivatives displayed increased potency. The three tested variants with substitutions of glycine to methionine in position 3 displayed reduced efficacy and are therefore considered as partial agonists. The two most promising activating candidates were further investigated for functional selectivity between the G-protein and the β-arrestin pathway, as well as for activation of mTOR. In the respective read-outs no difference was detected compared to wild-type DynB. Our data indicate, that assessment of affinity to KOPr alone is not sufficient to predict either potency or efficacy of peptidergic agonists on KOPr. Further assessment of downstream pathways is required to allow more reliable predictions of in vivo effects.